## if [a = d/b + d/c] then [d = a / (1/b + 1/c)]

Simplificatation, evaluation, linear equations, linear graphs, linear inequalities, basic word problems, etc.
gcmky
Posts: 2
Joined: Mon May 23, 2011 8:30 pm
Contact:

### if [a = d/b + d/c] then [d = a / (1/b + 1/c)]

I have an equation that is a = d/b + d/c . Supposedly this means that
d = a / (1/b + 1/c) is also true. How do you get from the first equation to the second?
Someone told me to factor out d first but I'm not sure how. Thanks.

stapel_eliz
Posts: 1628
Joined: Mon Dec 08, 2008 4:22 pm
Contact:
I have an equation that is a = d/b + d/c . Supposedly this means that
d = a / (1/b + 1/c) is also true. How do you get from the first equation to the second?
Someone told me to factor out d first but I'm not sure how. Thanks.
If you had "db + dc", would you be able to factor?

gcmky
Posts: 2
Joined: Mon May 23, 2011 8:30 pm
Contact:

### Re:

I have an equation that is a = d/b + d/c . Supposedly this means that
d = a / (1/b + 1/c) is also true. How do you get from the first equation to the second?
Someone told me to factor out d first but I'm not sure how. Thanks.
If you had "db + dc", would you be able to factor?
Think I got it. Thanks.

a = d/b + d/c
a = d(1/b) + d(1/c)
a = d(1/b + 1/c)
a/(1/b + 1/c) = d(1/b + 1/c) / (1/b + 1/c)
a/(1/b + 1/c) = d

stapel_eliz
Posts: 1628
Joined: Mon Dec 08, 2008 4:22 pm
Contact:
Think I got it. Thanks.

a = d/b + d/c
a = d(1/b) + d(1/c)
a = d(1/b + 1/c)
a/(1/b + 1/c) = d(1/b + 1/c) / (1/b + 1/c)
a/(1/b + 1/c) = d
Exactly! Good work!